Testing stellar yield prescriptions in omega+: implications for rising sodium abundances in young thick disc stars - Owusu, Evans; Ruiter, Ashley J; Kemp, Alex J; Buder, Sven; Seitenzahl, Ivo R; Rodriguez-Segovia, Nicolas; Pakmor, R; Cinquegrana, Giulia C; Storm, Nicholas; Eitner, Philipp; Bergemann, Maria (Monthly notices of the Royal Astronomical Society, 2026)
We recently identified an upturn in [Na/Fe] for the population of solar-type stars in the Galactic young thick disc ($-0.3 < \mathrm{[Fe/H]} < +0.3$ dex) at supersolar metallicity in GALAH (GALactic Archaeology with HERMES) data. Here, we investigate the cause of this unexplained Na enrichment ($[{\rm Na/Fe}] \approx 0 \!-\!0.6$ dex) using the omega+ Galactic chemical evolution code. We investigate the increase of [Na/Fe] with four combinations of nucleosynthetic yields from the literature, with source contributions from core-collapse supernovae (CC SNe), asymptotic giant branch (AGB) stars, and Type Ia supernovae (SNe Ia). We focus on two possible causes for the Na enhancement: the ‘metallicity effect’ resulting from CC SNe at supersolar metallicity and the contribution of metal-rich AGB stars. We adopt two sets of SN Ia yields with one model assuming only Chandrasekhar-mass explosions, and another assuming only sub-Chandrasekhar-mass explosions. We find that the assumed SN Ia explosion has little effect on the [Na/Fe] Galactic chemical evolution modelling, and all Galactic chemical evolution models tested fail to reproduce the observed [Na/Fe] enrichment in the young thick disc population at supersolar metallicities. Our study indicates a possible ‘underpollution effect’ by SNe Ia, which are the dominant producers of iron, in the Galactic disc’s solar-type star population. These findings provide a step forward towards understanding the origin of the unexplained sodium enrichment at supersolar metallicities in the Galactic disc.
Veröffentlicht: 24. November 2025
Gesehen am 17.02.2026